Various Language Expressions in The Criticism of Madurese People on Social Media Field - Akhmad Sofyan; Panakajaya Hidayatullah; Ali Badrudin (Institut Agama Islam Negeri Madura, 2020)
The Madurese community in Situbondo is a group of people who are still 'unfamiliar' with the internet media (social media). Their lack of understanding in using social media often creates problems in society. This article is the result of ethnography of communication research which discusses criticism behavior of Madurese people in Situbondo in social media. It comprehensively analyzes aspects of use of language choice, motive of language choice and language formulation expressed by informants. Research findings show that: 1) Situbondo people express criticism in social media by using code of Madurese language and mixed Madurese-Indonesia and Madurese-English, and they are expressed through some patterns which are humor, figurative, threatening and affirmative, direct and indirect satire, Kiyai quote and lyrical/poetical pattern; 2) Some motives background of choice of language code in expressing criticism are influenced by aspects of hierarchy in a context of diglosia society, politic of identity; dimension of ethnic group and psychological and cultural motives. Formulation of these findings explain that most of criticism model of Madurese people in Situbondo through social media is manifestation of habit in expressing criticism in real world. Something avoided is criticism model using sarcasm sentence, containing hate speech, offending pride, social status, family and feeling of interlocutors. Expressive and outspoken criticism in social media are also considered to be dangerous and unacceptable by people because they create ‘floating’ (unclear) interpretation, and potential to be misinterpreted. While some acceptable criticism are criticism model expressed by fine language and expressed by humor, figurative, fine satire and lyrical/poetical patterns.